Mewujudkan Pembangunan Yang Berkeadilan Di Provinsi Kepulauan Riau: Strategi Mengatasi Ketimpangan Antarwilayah - Akbar (Badan Perencanaan, Penelitian dan Pengembangan Pemerintah Provinsi Kepulauan Riau, 2025)
The Riau Islands Province has great potential due to its strategic location. However, up to this point, the Riau Islands Province still faces issues of Disparity in Development Among Regions. In the Regional Development Plan Document, uneven infrastructure, suboptimal human resource competitiveness, and weak coordination among stakeholders are considered to be the causes of the issues that occur. Using the USG method or Urgency, Seriousness, and Growth, uneven infrastructure received a score of 56 and was determined to be the main problem. Furthermore, strengthening infrastructure and regional connectivity, economic diversification, and empowerment of micro, small, and medium enterprises (MSMEs), as well as improving social services and human resources were selected as policy alternatives that can be taken by policymakers. Then, using the Analytical Hierarchy Process (AHP) method, Strengthening Infrastructure and Regional Connectivity received a score of 0.93 and was chosen as a policy recommendation that should be implemented immediately by decision-makers.